Awareness and Practices on Disaster Preparedness of Students of a Public High School in Antique - Gerry L. Ventura; Dennis V. Madrigal (Philippine Social Science Journal, 2020)
Disasters cause deaths and serious disruptions in society, which call for the global community to take drastic steps to address and reduce the impacts of these inevitable calamities. That is why the government, through the Philippine Disaster Risk Reduction Management Act of 2010, requires the integration of disaster risk reduction in the school curriculum to strengthen the awareness and practice of personnel and students on calamity preparedness. Hence, the paper assessed the level of awareness and extent of practice on disaster preparedness before, during, and after the disaster of public junior high school students in Antique. Likewise, it sought to establish a difference in awareness and practice on disaster preparedness relative to sex, residence, and grade level and the relationship between awareness and practice.